Stakeholder insights into athlete attrition in the high-performance pathway - Guevara, S. A.; Donaldson, A.; Keegan, R. J.; Appaneal, R. N.; Smyth, E. A.; Waddington, G.; Mahony, K.; Drew, M. K. (Journal of Science and Medicine in Sport, 2022)
Objectives: Primary: To gain a system-wide perspective on factors leading to athlete attrition from a high-performance sport system (HPSS). Secondary: To identify what a sample of system-wide stakeholders and past athletes value as the most important and feasible attrition factors to address to retain talented athletes. Design: Mixed-methods. Methods: Concept mapping was used for qualitative data collection and quantitative data analysis. Sixty-one participants including: (i) past athletes from an Australian state sporting institute; (ii) their families; and (iii) internal and external stakeholders to a HPSS who supported past athletes. Results: Participants brainstormed 83 unique statements (i.e. attrition factors) that were mapped into 13 clusters of attrition factors following multidimensional scaling and hierarchical cluster analysis performed on the participants sorting data: `abuse and mismanagement of health`; `athlete health`; `limited support/resourcing`; `coaching`; `inconsistent processes`; `financial and career support`; `pathway structure`; `organisational dynamics`; `competitive stress`; `performance potential`; `challenges with selection and transition`; `psychological state`; and `competing non-sport priorities`. `Abuse and mismanagement of health` had the highest mean importance (3.76 out of 5) and feasibility (3.31) rating. The 13 clusters were further grouped into four overarching domains: `sport system policy, structure and processes`; `pathway structure, transition and support`; `individual athlete health and capability`; and `whole-of-life demands and priorities`. The domain `sport system policy, structure and processes` contained the most important and feasible clusters. Conclusions: Macro (system-level) and micro (intrapersonal and interpersonal) level athlete attrition factors should be considered together. Athlete health was considered the most important athlete retention issue to address.